The ‘Shell Bill’ Game: Avoidance and the Origination Clause - Rebecca M. Kysar (Washington University Law Review, 2014)
With increasing frequency, many important revenue laws, such as the Affordable Care Act and the American Taxpayer Relief Act of 2012, begin as “shell bills.” The Origination Clause of the Constitution aims to place decisions over tax policy closer to the people by requiring that bills raising revenue begin in the House of Representatives, but the Clause also allows the Senate to amend such bills. The Senate has interpreted its amendment power broadly, striking the language of a bill passed by the House (the shell bill), and replacing it entirely with its own unrelated revenue proposal. According to a new challenge against the Affordable Care Act, this shell bill game is an unconstitutional sleight of hand because it obfuscates the bill’s true origins in the Senate. The constitutional fate of the Affordable Care Act and myriad other revenue laws, as well as the intra-congressional balance of power over revenue policy, turns on the interpretation of the Senate’s power to amend revenue legislation, an analysis heretofore unexplored in the academic literature. This Article draws upon constitutional text, history, and congressional and judicial precedent to conclude that such amendment power is broad and, accordingly, that revenue laws that began as shell bills do not violate the Origination Clause. This Article also proposes a conceptual framework for analyzing existing jurisprudence interpreting the Origination Clause—a “legislative process avoidance” doctrine, whereby the Court deflects searching review of lawmaking procedures. Grounded in constitutional text and history, theories of judicial review, and longstanding principles guarding congressional purview over internal rules, this legislative process avoidance doctrine further supports deference to the Senate’s expansive interpretation of its amendment power without rendering the Clause a nullity. Separation of powers concerns also show the doctrine’s promise in other constitutional contexts, such as the interpretation of gaps in the lawmaking process left open by Article 1, Section 7.
Keywords: Origination Clause; Affordable Care Act; shell bill